Changes in the Distribution of Individual Earnings in the United States: 1967-1986 - Karoly, Lynn A. (The Review of Economics and Statistics, 1992)
Using micro-data from the Current Population Survey, the author examines the sensitivity of conclusion regarding time-series changes in inequality to the measure of inequality employed and to the population group analyzed. Although changes in inequality over time are sensitive to the measure of inequality, the author finds a general pattern of stable or decreasing inequality throughout the 1970s followed by a period of increasing inequality. Based upon a decomposition analysis, the author concludes that these changes are not simply the results of the changing employment distribution among groups, defined by sex, age, education or industry. Instead the rise in inequality results from an increase in inequality within these groups. Copyright 1992 by MIT Press.